ANALYSIS OF REGIONALLY-GEOGRAPHICAL AND LATITUDINAL-ZONAL STRUCTURES OF FOREST FLORAE (THE CASE OF WOODLAND “LARGE FOREST”) - Bondaruk, M. A.; Tselishchev, A. G. (Forestry and Forest Melioration, 2018)
Introduction The importance of geographical analysis of forest flora as a component of modern system approach for investigations of phytodiversity within forest areas and methodical support of forest biodiversity monitoring system is substantiated. The diversity of geographical elements (geo elements) of flora (groups of species similar by geographical distribution and origin) represents both the historical development features of flora in the certain forestland, district or region and adaptive possibilities of its species. Investigation relevance is caused by the international obligations of Ukraine in relation to biodiversity conservation, an establishment of forest monitoring system and sustainable forest management. Materials and methods The object of the research is forest flora in woodland “Large Forest” located within southern part of Left-bank forest-steppe zone of Ukraine. The inventory of vegetation species composition was carried out in 24 subcompartments with oak stands of natural (vegetative and seed) origin of middle-aged and senior-aged classes in dry, fresh and moist maple-linden fertile oak forest type (0,980 km2) and 1 subcompartment (area of 0,039 km2) with middle-aged alder stands of vegetative origin in wet black alder fertile site type. The scheme of H. Meusel with co-authors was used as the basis for classification of the types of plant species areals (regional and geographical and latitudinal-zonal) in the forestland. The absolute and relative values of richness with the species of zonal and regional flora geo elements were investigated. Species distribution within Ukraine was pointed according to the natural zones and administrative-territorial units. Simultaneous comparison of geographical structure of flora for two forest formations, Querceta roboris and Alneta glutinosae (according to the Ukrainian dominant classification), and two vegetation classes, Querco-Fagetea and Alneta glutinosae (according to the Braun-Blanquet syntaxonomic classification), was executed in relation to general geographical spectrum of forest flora within the investigated woodland area. The analysis of areals provides as well the identification of relict and endemic species, species on the areal boundaries, species widespread and narrow-spread within Europe, its adjoining territories and Ukraine, and adventitious species. Results The zonal analysis of areas of species represented within the forestland testifies that leading positions are occupied by temperate species of broadleaved forests (50.6 %); boreal species of coniferous forests and also pratal and paludous coenosises rank next (45.4 %). There is some greater percent of temperate elements in oak forest formation and boreal elements and absence of temperate elements in alder forest formation. Some species from herbaceous layer are arctic-meridional, plural-zonal and adventitious (1, 2 and 1, respectively). An adventitious element presents only 1.1 % of forest flora; however, the establishment of monitoring on potentially possible adventization of forest floristic composition is required. The regionally-geographical spectrum of flora in the forestland is presented mainly by the group of species with the European areal (39.4 %) which is characteristic for florae of modern European Forest-steppe and Left-bank Forest-steppe of Ukraine and is a basis for a flora of broad-leaved nemoral formations. The majority of species with European and European-Western-Siberian areals and all Eastern European group are widespread in the ecosystems of oak forests. The European-Siberian species are recorded only in alder forests, that indicates the connection of Alneta glutinosae formation geo elements with Northern (Polissya) florae. The European species prevail in the leading zonal temperate element including 6 species (Corydalis solida (L.) Clairv., Corydalis marschalliana Pers., Scilla sibirica L., Galium odoratum (L.) Scop., Asarum europaeum L., Aconitum lasiostomum Reichenb.) which are the relics of Atlantic period. The boreal element is represented mainly by the large areal species of the European-Asian origin, among which 4 species (Angelica sylvestris L., Arabis pendula L., Actaea spicata L., Equisetum sylvaticum L.) belong to the relics of Wurm period. Six species of herbaceous plants (Aconitum lasiostomum Reichenb., Arabis pendula L., Veronica capsellicarpa Dubovik, Corydalis marschalliana Pers., Scilla sibirica L., Tulipa quercetorum Klok. et Zoz) have areals within forest-steppe and part of the steppe zones of Ukraine. One species (Tulipa quercetorum Klok. et Zoz) is endemic to the Southern European part of Ukraine with national and international conservation statuses. Conclusions Research of regionally-geographical and latitudinal-zonal structure of forest flora is the important component of a system approach for investigations of phytodiversity within forest areas and methodical support of forest biodiversity monitoring system. The analysis of areals of relict and endemic species, species on the areal boundaries, species wide-spread and narrow-spread within Europe, its adjoining territories and Ukraine, and also adventitious species assists the identification of features of forest flora historical development and forest biodiversity conservation.